Synchrotron study of metal localization in Typha latifolia L. root sections. (14th October 2015) - Qian, Yu; Feng, Huan; Gallagher, Frank J.; Zhu, Qingzhi; Wu, Meiyin; Liu, Chang‐Jun; Jones, Keith W.; Tappero, Ryan V.
Abstract : Understanding mechanisms that control plant root metal assimilation in soil is critical to the sustainable management of metal‐contaminated land. With the assistance of the synchrotron X‐ray fluorescence technique, this study investigated possible mechanisms that control the localization of Fe, Cu, Mn, Pb and Zn in the root tissues of Typha latifolia L. collected from a contaminated wetland. Metal localizations especially in the case of Fe and Pb in the dermal tissue and the vascular bundles were different. Cluster analysis was performed to divide the dermal tissue into iron‐plaque‐enriched dermal tissue and regular dermal tissue based on the spatial distribution of Pb and Fe. Factor analysis showed that Cu and Zn were closely correlated to each other in the dermal tissues. The association of Cu, Zn and Mn with Fe was strong in both regular dermal tissue and iron‐plaque‐enriched dermal tissue, while significant ( p < 0.05) correlation of Fe with Pb was only observed in tissues enriched with iron plaque. In the vascular bundles, Zn, Mn and Cu showed strong association, suggesting that the localization of these three elements was controlled by a similar mechanism. Iron plaque in the peripheral dermal tissues acted as a barrier for Pb and a buffer for Zn, Cu and Mn. The Casparian strip regulated the transportation of metals from dermal tissues to the vascular bundles. The results suggested that the mechanisms controlling metal localization in root tissues varied with both tissue types and metals.